Gender Characteristics of Individual's Linguistic Behavior in the Context of Future Translators' Professional Training - Ihor Bloshchynskyi; Hanna Bahrii; Lidiia Nanivska; Larysa Tsviak; Ilona Isaieva; Kateryna Skyba; Svitlana Pilishek; Nadiia Moroz; Oksana Herasimova; Valentyna Yamkova; Iryna Mishchynska (Emerging Science Journal, 2022)
The article seeks to investigate the gender differences of individuals in foreign language learning and reveals the peculiarities of the implementation of linguistic behaviour in the context of a gender role approach in the process of foreign language teaching to future translators. The purpose of the article is to analyze the gender differences in the implementation of future interpreters' linguistic behavior, to develop and check the program of their foreign language skills development, and to make practical recommendations for improving the professional training, taking into account the gender peculiarities. Methods of research: theoretical, empirical, psychodiagnostic, and testing methods. The study reveals the main gender differences in the teaching of both male and female students, with a focus on the peculiarities of their perception, thinking, and foreign language abilities in general. The program and practical recommendations to foreign language instructors on the foreign language ability development of future interpreters are presented in the article based on a gender approach. The results of the research indicate that gender does affect foreign language learning styles. It has been found that considerable attention should be paid to overcoming the gender gap in the educational achievements of male and female future translators. Therefore, the authors consider it appropriate to teach a foreign language in mixed groups without dividing male and female students into separate subgroups. Doi: 10.28991/ESJ-2022-SIED-014 Full Text: PDF